Tecniche per la lettura ad alta voce 27 suggerimenti per la fascia 0-6 anni - Batini, Federico (Storie per le persone e le comunità, 2021)
This book presents 27 operational techniques useful for making the practice of reading aloud as effective as possible in the educational structures dealing with children up to 6 years of age, by following a bottom-up approach. The methodological proposals are organised in three sections: Gaining and Developing Attention, Creating Interest in Stories and Encouraging Participation and Book Culture. The research took into account hundreds of suggestions formulated by scholars, educators and teachers who are experts in reading aloud, as well as by a group of researchers. It explored the specialised bibliography and websites dedicated to reading aloud and involved, through interviews, educators and teachers of nursery schools and preschools from the 35 Education Zones of the Region of Tuscany. The aim is to promote, in all children and youth, the development of the basic skills needed to achieve academic success of each and every one.